Essential Features of Responsible Governance of Agricultural Biotechnology - Hartley, Sarah; Gillund, Frøydis; van Hove, Lilian; Wickson, Fern (PLOS Biology, 2016)
Agricultural biotechnology continues to generate controversy, and new approaches to governance are needed for the next generation of techniques and applications. This Perspective proposes five essential features of responsible governance.